Origins and functional evolution of Y chromosomes across mammals - Cortez, Diego; Marin, Ray; Toledo-Flores, Deborah; Froidevaux, Laure; Liechti, Angélica; Waters, Paul D.; Grützner, Frank; Kaessmann, Henrik (Nature, 2014)
Y chromosomes underlie sex determination in mammals, but their repeat-rich nature has hampered sequencing and associated evolutionary studies. Here we trace Y evolution across 15 representative mammals on the basis of high-throughput genome and transcriptome sequencing. We uncover three independent sex chromosome originations in mammals and birds (the outgroup). The original placental and marsupial (therian) Y, containing the sex-determining gene SRY, emerged in the therian ancestor approximately 180 million years ago, in parallel with the first of five monotreme Y chromosomes, carrying the probable sex-determining gene AMH. The avian W chromosome arose approximately 140 million years ago in the bird ancestor. The small Y/W gene repertoires, enriched in regulatory functions, were rapidly defined following stratification (recombination arrest) and erosion events and have remained considerably stable. Despite expression decreases in therians, Y/W genes show notable conservation of proto-sex chromosome expression patterns, although various Y genes evolved testis-specificities through differential regulatory decay. Thus, although some genes evolved novel functions through spatial/temporal expression shifts, most Y genes probably endured, at least initially, because of dosage constraints.